Determination of non-steroidal antiinflammatory drugs in equine biological samples by chromatographic methods [Yarış atlarında kullanımı suistimal edilen bazı non-steroidal antienflamatuvar ilaçların biyolojik örneklerden kromatografik yöntemlerle miktar tayini] - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (Marmara University, 2012)
In the knowledge that non-steroidal antiinflammatory drugs (NSAIDs) which are not included in the WADA's (World Anti-Doping Agency) list enacting doping substances and methods, have been abused in horse racing; a review on qualitative and quantitative determination of some of these non-steroidal antiinflammatory drugs (acetylsalicyclic acid, benzydamine, bufexamac, diclofenac sodium, diflunisal, eltenac, etodolac, etoricoxib, felbinac, phenylbutazone, flufenamic acid, flunixin, flurbiprofen, ibuprofen, indometacin, indoprofen, carprofen, ketoprofen, ketorolac, meclofenamic acid, mefenamic acid, meloxicam, mofebutazon, naproxen, niflumic acid, nimesulide, oxyphenbutazone, piroxicam, ramifenazone, selecoxib, sulindac, tenoxicam, tiaprofenic acid, tolfenamic acid, tolmetin, valdecoxib and vedaprofen) from biological samples of horses was gathered within the context of this work.
Keywords: Chromatography; Drug monitoring; Horse; Non-steroidal antiinflammatory drugs